Analisis Daya Elektrik dan Efisiensi dengan Variasi Debit Air dan Sudut Kemiringan Turbin pada Turbin Ulir Archimedes Dua Sudu - Frans Ivan Christofel Hutabarat; Andre Amba Matarru; Gad Gunawan (Infotekmesin, 2023)
This study analyzes the effect of water discharge and the angle of inclination of the turbine on electrical power and efficiency using Archimedes screw turbine with two blades. This study aims to determine the effect of water discharge and the angle of inclination of the turbine on the electrical power and efficiency of the two-blade Archimedes screw turbine. The turbine is fed with water at variations of water discharge of 150 l/m, 300 l/m, 450 l/m. And vary angle of inclination of the turbine of 35°, 40°, and 45°. By using the variation of the water discharge that has been mentioned, the electrical power and efficiency obtained are 1,24 W and 9,78 % at a variation of 150 l/m, 2,89 W and 10,77 % at a variation of 300 l/m, and 3,65 W and 9,06 % at a variation of 450 l/m. When varying the angle of inclination, the electrical power and efficiency obtained are 3,33 W and 10,77 % on a slope of 35°, 3,65 W and 10,53 % on a slope of 40°, and 3,15 W and 8,6 % on a variation of 45°.